2011
DOI: 10.2147/ppa.s22117
|View full text |Cite
|
Sign up to set email alerts
|

Public’s attitudes towards community pharmacy in Qatar: a pilot study

Abstract: ObjectivesTo assess the public’s attitudes towards the community pharmacist’s role in Qatar, to investigate the public’s use of community pharmacy, and to determine the public’s views of and satisfaction with community pharmacy services currently provided in Qatar.Materials and methodsThree community pharmacies in Qatar were randomly selected as study sites. Patients 16 years of age and over who were able to communicate in English or Arabic were randomly approached and anonymously interviewed using a multipart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
171
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(197 citation statements)
references
References 20 publications
20
171
6
Order By: Relevance
“…This is in line with other studies that have investigated public's attitudes towards community pharmacies in Middle East countries. 7,15,17 Therefore, it can be inferred that access to community pharmacies in these countries did not appear to be an important barrier for utilizing the given services as has been identified for other populations. 18,19 Efficient public-pharmacist contact is essential to improve the use of medication and ensure optimal therapy outcomes.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This is in line with other studies that have investigated public's attitudes towards community pharmacies in Middle East countries. 7,15,17 Therefore, it can be inferred that access to community pharmacies in these countries did not appear to be an important barrier for utilizing the given services as has been identified for other populations. 18,19 Efficient public-pharmacist contact is essential to improve the use of medication and ensure optimal therapy outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…Previous research has shown that these services are important for the development of pharmacist-primary care collaboration. 11,17,20 Overall, findings from this study describe the current use of community pharmacies and the general image towards the role of pharmacists in Iraq.…”
Section: Innovations In Pharmacymentioning
confidence: 80%
See 1 more Smart Citation
“…A study looking at the public's view of community pharmacies in Qatar found 50% of the public rated their physician as the primary source of drug information and 45% trusted the drug information provided by the physician over the pharmacist. 7 In addition, many community pharmacy preceptors graduated from countries where the focus is predominately on the business of pharmacy rather than the practice of pharmacy. This may have influenced these pharmacists' responses.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed around the world to evaluate practice and the application of pharmaceutical care in community pharmacy setting [5,6,7,8]. A study done in Canada concluded that many pharmacists in community settings have not yet been able to implement pharmaceutical care as part of their routine work activities, a small number of pharmacists appeared to be introducing pharmaceutical care into the practice setting [5].…”
Section: Introductionmentioning
confidence: 99%